The Effect of Using Speedy English Grammar Application towards Students' Grammar Mastery in Simple Past Tense at the Twelfth Grade of SMK Walisongo Menes Pandeglang Banten in Academic Year 2023/2024 - Najilah, Ifa; Sudirman, Ade; Munawaroh, Tatu (Journal of English Education Studies, 2024)
The objective of this research is to investigate the significant effect of using Speedy English Grammar application towards students' grammar mastery in simple past tense at the twelfth grade of SMK Walisongo. The research approach used was a quantitative approach and quasi experimental method with achievement test in collecting the data. Achievement test included pre-test and post-test. This research was conducted at the twelfth grade of SMK Walisongo Menes. The samples of this research were 40 students that consisted of 20 students of experimental and 20 students of control class. The experimental class used Speedy English Grammar and the control class used English Grammar and Test application. The data was analyzed by using statistical of program SPSS 22. Based on the result of data analysis, the result showed that mean of post-test both experimental and control class different were 76.70 and 70.45, and for the result of t-test obtained sign score 0.000 ≤ α = 0.05. The result indicated the alternative hypothesis was accepted and the null hypothesis was rejected. As the result there was significant effect of using the Speedy English Grammar application towards students’ grammar mastery in simple past test at the twelfth grade of SMK Walisongo Menes.